2013
DOI: 10.4103/2152-7806.121612
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive management of adult craniopharyngiomas: An analysis of our series and review of literature

Abstract: Background:Craniopharyngiomas (CPs) are slow growing tumors with an incidence of between 1.2% and 4.6%, having a bimodal age distribution typically peaking in childhood and in adults between 45 and 60 years. Recurrences occur even after documented gross total resections necessitating a combination of therapeutic strategies. Obtaining a cure of this tumor in adults without producing major side effects continues to remain elusive.Methods:We describe our results in 11 patients with CP treated in a minimally invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…8 This is evident in multiple case series in which recurrence rates range from 24.8-100% after performing STR, as compared to recurrence rates ranging from 0-52.1%% after GTR (Table 1, follow-up 2.2-10 years). 6,7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In 1996 Eldevik et al examined only CP patients who underwent STR and reported that the addition of radiation reduced recurrence from 85.6% to 35%. 15 Multiple other studies have corroborated this finding, demonstrating that the addition of RT to STR reduced recurrence rates to 14-37.5%, which is comparable to the recurrence rates achieved after GTR in multiple series.…”
Section: Gtr Versus Str Recurrence Ratesmentioning
confidence: 99%
“…8 This is evident in multiple case series in which recurrence rates range from 24.8-100% after performing STR, as compared to recurrence rates ranging from 0-52.1%% after GTR (Table 1, follow-up 2.2-10 years). 6,7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In 1996 Eldevik et al examined only CP patients who underwent STR and reported that the addition of radiation reduced recurrence from 85.6% to 35%. 15 Multiple other studies have corroborated this finding, demonstrating that the addition of RT to STR reduced recurrence rates to 14-37.5%, which is comparable to the recurrence rates achieved after GTR in multiple series.…”
Section: Gtr Versus Str Recurrence Ratesmentioning
confidence: 99%
“…Previous evidence investigated ORS in managing CP, it was predominantly of cystic type, [18][19][20][21] and others were of mixed type (partially cystic and partially solid). 22 In our cases, 73% needed no re-aspiration, 19% of patients needed re-aspiration every 6 months, and 8% needed it every 3 months but remained stable without symptoms of increased ICP.…”
Section: Discussionmentioning
confidence: 50%
“…In our study, all cases were of the enhanced cystic type, three cases were of a calcified wall, and four cases presented with hydrocephalus that needed a VP shunt. Previous evidence investigated ORS in managing CP, it was predominantly of cystic type, 18‐21 and others were of mixed type (partially cystic and partially solid) 22 . In our cases, the tumour cysts appear to stabilize after catheter placement without the need for repeated aspirations; of the 12 patients included, only one case needed re‐aspiration since the cyst size on follow‐up increased.…”
Section: Discussionmentioning
confidence: 59%
“…Intraoperative fenestration of the cyst wall usually drains the dense liquid content, typically described as 'engine oil' in color and texture [2]; spillage of the cyst contents into spaces containing cerebrospinal fluid (CSF) may lead to chemical meningitis and possibly secondary hydrocephalus [32]. Some authors advocate inserting a catheter with an Ommaya reservoir to allow for intermittent drainage, combined with radiation therapy [51]; long-term catheter placement, however, is associated with risks of infection, catheter displacement, content re-accumulation due to cyst septations, and pain with Ommaya reservoir tapping. Remarkably, none of the NTVA studies summarized in Table 1 The low complication and recurrence rates (Table 1 and Table 3) following NTVA, as well as the endoscopic endonasal approach, compared to microsurgery and Ommaya reservoir insertion, support the validity of these minimally invasive techniques as credible and potentially better alternatives in the management of CC or cystic-dominant craniopharyngiomas.…”
Section: Discussionmentioning
confidence: 99%